Gamification and Student Engagement: A Comparative Study Between Intrinsic and Extrinsic Motivation - Rinovian Rais; Moussa Traore; Aissatou Diallo (Journal of Paddisengeng Technology, 2026)
Background. Gamification has emerged as an innovative pedagogical approach to enhance student engagement by integrating game-based elements such as rewards, points, and challenges into learning environments. Existing studies predominantly emphasize its effectiveness in increasing participation; however, limited attention has been given to how gamification differentially influences intrinsic and extrinsic motivation as key drivers of engagement. Purpose. This study aims to examine the comparative effects of gamification on intrinsic and extrinsic motivation and to analyze how these motivational dimensions subsequently impact student engagement in educational settings. Method. A mixed-methods research design was employed, combining quantitative and qualitative approaches. Survey data were collected to measure students’ intrinsic and extrinsic motivation levels before and after exposure to gamified learning environments. In addition, semi-structured interviews were conducted to capture in-depth student perspectives on their motivational experiences. Results. The findings demonstrate that gamification significantly enhances both intrinsic and extrinsic motivation. Students exposed to gamified learning showed a 0.7-point increase in intrinsic motivation and a 0.5-point increase in extrinsic motivation compared to the control group. Qualitative insights further reveal that gamified elements not only increase enjoyment and interest in learning but also reinforce goal-oriented behaviors through structured rewards and feedback mechanisms. Conclusion. Gamification serves as an effective strategy for fostering student engagement by simultaneously addressing intrinsic enjoyment and extrinsic incentives. The results highlight the importance of designing balanced gamified learning environments that accommodate diverse motivational factors. Educators are encouraged to strategically integrate gamification elements to optimize both participation and learning outcomes.